Mechanistic insight into the disruption of Tau R3–R4 protofibrils by curcumin and epinephrine: an all-atom molecular dynamics study. Issue 34 (22nd August 2022) - Zou, Yu; Qi, Bote; Tan, Jingwang; Sun, Yunxiang; Gong, Yehong; Zhang, Qingwen
Abstract : Binding mechanisms of Tau pentamer by curcumin and epinephrine. Abstract : The accumulation of Tau protein aggregates is a pathological hallmark of tauopathy, including chronic traumatic encephalopathy (CTE). Inhibiting Tau aggregation or disrupting preformed Tau fibrils is considered one of the rational therapeutic strategies to combat tauopathy. Previous studies reported that curcumin (Cur, a molecule of a labile natural product) and epinephrine (EP, an important neurotransmitter) could effectively inhibit the formation of Tau fibrillar aggregates and disassociate preformed fibrils. However, the underlying molecular mechanisms remain elusive. In this study, we performed multiple molecular dynamics simulations for 17.5 μs in total to investigate the influence of Cur and EP on the C-shaped Tau protofibril associated with CTE. Our simulations show that the protofibrillar pentamer is the smallest stable Tau R3–R4 protofibril. Taking the pentamer as a protofibril model, we found that both Cur and EP molecules could affect the shape of the Tau pentamer by changing the β2–β3 and β7–β8 angles, leading to a more extended structure. Cur and EP display a disruptive effect on the local β-sheets and the formation of hydrogen bonds, and thus destabilize the global protofibril structure. The contact number analysis shows that Cur has a higher binding affinity with the Tau pentamer than EP, especially in the nucleating segment PHF6. Hydrophobic, π–π and cation–π interactions together facilitate the binding of Cur and EP with the Tau pentamer. Cur exhibits stronger hydrophobic and π–π interactions with Tau than EP, and EP displays a stronger cation–π interaction. Our findings provide molecular insights into the disruptive mechanisms of the Tau R3–R4 protofibrils by curcumin and epinephrine, which may be useful for the design of effective drug candidates for the treatment of CTE.